METHOD OF HUMIDITY CONTROL IN THE CYBER-PHYSICAL SYSTEM “SMART HOME” - ALEKSOV, SERHII; HOVORUSHCHENKO, TETIANA; VOICHUR, YURIY; BOYARCHUK, ARTEM (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The most important thing today is to ensure automatic control of a smart home. A “smart home” is a set of solutions that automate everyday activities, relieving the owner of routine tasks. A “smart home” is not a set of devices that are controlled remotely, but a unified system for managing such devices (an ecosystem) that provides specific benefits to the user, such as visibility of control, convenience, and saving time and effort. Thus, the cyber-physical ecosystem of a Smart home should perform certain actions in response to specific situations without human intervention. At the same time, such a cyber-physical system should not require deep knowledge of programming and computer engineering from residents, and should be able to recognize situations and make the necessary decisions depending on the situation. Therefore, it is currently an urgent task to ensure the possibility of automatic decision support in the cyber-physical system “Smart Home”. The study of known methods and tools has shown that existing solutions usually do not provide for fully automatic humidity control in a Smart Home, but are focused either on fully user-controlled control or automatic control along with manual control (using a mobile application, control via the Internet, etc.). Therefore, the purpose of this study is to support decision-making in the humidity control subsystem of the cyber-physical system “Smart Home” in order to ensure fully automatic control of such a subsystem. The developed method of humidity control in the cyber-physical system “Smart Home” allows to introduce the necessary parameters for further automatic functioning of the humidity control subsystem in residential premises of various types. The developed method of humidity control in the cyber-physical system “Smart Home” provides a comfortable (taking into account building and sanitary and hygienic standards) moisture concentration in the air environment of the corresponding dwelling.